2014
DOI: 10.1080/01919512.2014.904735
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nano-Metal Oxides on Bromate Formation during Ozonation Process

Abstract: Simulation studies in pure water were conducted to investigate the effect of nano-metal oxides on bromate (BrO 3 − ) formation as catalysts and the catalytic mechanism. Results indicated that compared to ozonation alone, both nano-SnO 2 and nano-TiO 2 could inhibit the formation of bromate during ozonation process. The inhibition efficiency of BrO 3 − formation by nano-TiO 2 enhanced with the increasing of ozone dosage and the decreasing of nano-TiO 2 dosage, Br − concentrations and the pH value. Possible BrO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Wu et al [27] conducted simulation studies to investigate the influence of nano-metal oxides, SnO2 and TiO2 on bromate generation in pure water during ozone treatment. Their results showed that ozonation in the presence of nano-metal oxides (SnO2 and TiO2) as catalysts, minimized BrO3 generation to a greater extent, compared to single ozonation.…”
Section: Bromate Minimization Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Wu et al [27] conducted simulation studies to investigate the influence of nano-metal oxides, SnO2 and TiO2 on bromate generation in pure water during ozone treatment. Their results showed that ozonation in the presence of nano-metal oxides (SnO2 and TiO2) as catalysts, minimized BrO3 generation to a greater extent, compared to single ozonation.…”
Section: Bromate Minimization Strategiesmentioning
confidence: 99%
“…Wu et al [27] monitored BrO3 formation at different pH values during single ozonation and ozonation with nano-TiO2. Their results indicated that ozonation with nano-TiO2 favoured the formation of BrO3 as solution pH increased initially from 6.0 to 7.9.…”
Section: Factors Affecting Bromate Minimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, nanozinc oxide, nanotitanium dioxide, nanomagnesium oxide, and other nanosized metal oxides of the main element of the second cycle and the third cycle of the subgroup elements have a wider application range and greater influence. [19][20][21][22] Rao et al 23 found that the mechanical properties of polyvinyl alcohol composite film with copper oxide nanoparticles as filler were enhanced.…”
Section: Introductionmentioning
confidence: 99%